(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
This article examines the essence, formation regularities and manifestation features of the concepts of idea and ideology in society from a philosophical and socio-theoretical perspective. The purpose of the research is to substantiate the idea as a meaning-producing element of social consciousness and ideology as a complex communicative, cultural and institutional mechanism that systematizes ideas, legitimizes collective orientations and directs them toward social practice. The article synthesizes classical and contemporary theories of ideology, social constructivism, discourse analysis, legitimacy theory and approaches related to national idea, civil society, spiritual stability and the digital information environment. The findings show that ideas and ideologies do not emerge randomly; they are formed under the influence of historical needs, social interests, communicative conditions, institutional continuity, value systems and cultural memory. The manifestation of ideological processes can be observed through political institutions, education, mass media, religious and spiritual life, digital networks and everyday social practices. The research argues that in a democratic society ideology should not be reduced to a closed dogma; it must function as an open normative and communicative system that balances national interests, human dignity, rule of law, freedom of conscience and constructive pluralism of thought.